Comparison of the management recommendations of the Kaiser Permanente neonatal early-onset sepsis risk calculator (SRC) with NICE guideline CG149 in infants ≥34 weeks' gestation who developed early-onset sepsis. Issue 6 (13th March 2020) - Morris, Rachel; Jones, Steve; Banerjee, Sujoy; Collinson, Andrew; Hagan, Hannah; Walsh, Hannah; Thornton, Graham; Barnard, Ian; Warren, Chris; Reid, Jennifer; Busfield, Alison; Matthes, Jean
Abstract : Objective: To compare the management recommendations of the Kaiser Permanente neonatal early-onset sepsis risk calculator (SRC) with National Institute for Health and Care Excellence (NICE) guideline CG149 in infants ≥34 weeks' gestation who developed early-onset sepsis (EOS). Design: Retrospective multicentre study. Setting: Five maternity services in South West of England and Wales. Patients: 70 infants with EOS (<72 hours) confirmed on blood or cerebrospinal fluid culture. Methods: Retrospective virtual application of NICE and SRC through review of maternal and neonatal notes. Main outcome measure: The number of infants recommended antibiotics by 4 hours of birth. Results: The incidence of EOS ≥34 weeks was 0.5/1000 live births. Within 4 hours of birth, antibiotics were recommended for 39 infants (55.7%) with NICE, compared with 27 (38.6%) with SRC. The 12 infants advised early treatment by NICE but not SRC remained well, only one showing transient mild symptoms after 4 hours. Another four babies received antibiotics by 4 hours outside NICE and SRC guidance. The remaining 27 infants (38.6%) received antibiotics when symptomatic after 4 hours. Only one infant who was unwell from birth, died. Eighty-one per cent of all EOS infants were treated for clinical reasons rather than for risk factors alone. Conclusion: While both tools were poor in identifying EOS within 4 hours, NICE was superior to SRC in identifying asymptomatic cases. Currently, four out of five EOS have symptoms at first identification, the majority of whom present within 24 hours of birth. Antibiotic stewardship programmes using SRC should include enhanced observation for infants currently treated within NICE guidance.